BID’AH DALAM KEHIDUPAN BERKELUARGA MENURUT KITAB AL HABIB USMAN BIN ABDULLAH BIN ‘AQIL BIN YAHYA - Triwahyuni, Firly; Niken, Niken; Asvania, Selvy; Utami, Tera (Fakultas Dakwah dan Komunikasi Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Abstract: The difference in understanding among Muslims is a social and historical reality that has been going on since the first time after the death of Rasulullah SAW. This is caused by the conflict of interpretation in understanding religious texts. One of the religious terms that is always popular in modern times, namely